EFL Students’ Attitude toward Collaborative Strategic Reading in Reading Classroom - Hanifah Oktarina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
Focusing on attitude toward teaching strategies and promoting collaboration in teaching reading have been widely acknowledged to have impact on students’ achievement and attitude. This study explores the students’ attitude toward the implementation of CSR. Conducted under qualitative research design, this study involved 21 high school students who were classified into low- and high-achievers. To collect the data, the study administered a set of instruments: questionnaire, and interview. The data from the questionnaire were analysed by determining the means of the items and percentages of the students’ responses, and the interview data were analysed qualitatively. The findings from questionnaire and interview were in line with the students’ reading performance in which the high achievers gave more “agree” responses. They believed that CSR helped them develop their reading comprehension in terms of determining main idea, and increasing vocabularies. However, for the low achieving group, the only effect of CSR was the acknowledgement of its contribution to their increase in vocabulary. The study offers recommendations for teaching practice as well as for further research.